The SAMI Galaxy Survey: disc–halo interactions in radio-selected star-forming galaxies. Issue 2 (6th July 2017) - Leslie, S. K.; Bryant, J. J.; Ho, I.-T.; Sadler, E. M.; Medling, A. M.; Groves, B.; Kewley, L. J.; Bland-Hawthorn, J.; Croom, S. M.; Wong, O. I.; Brough, S.; Tescari, E.; et al.
Abstract: In this paper, we compare the radio emission at 1.4 GHz with optical outflow signatures of edge-on galaxies. We report observations of six edge-on star-forming galaxies in the Sydney-AAO Multiobject Integral-field spectrograph Galaxy Survey with 1.4 GHz luminosities >1 × 10 21 W Hz −1 . Extended minor axis optical emission is detected with enhanced [N ii ]/H α line ratios and velocity dispersions consistent with galactic winds in three of six galaxies. These galaxies may host outflows driven by a combination of thermal and cosmic ray processes. We find that galaxies with the strongest wind signatures have extended radio morphologies. Our results form a baseline for understanding the driving mechanisms of galactic winds.